2005
DOI: 10.1002/hed.20200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of genetically diagnosed lymph node micrometastasis for patients with oral squamous cell carcinoma

Abstract: These results indicate that a high rate of micrometastasis in cervical lymph nodes of oral SCCs and patients with multiple or lower neck spread of micrometastases have a poor prognosis; they should be treated with postoperative adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…Nieuwenhuis et al found that the survival of patients with cN0 but with one or more micrometastases (detected by molecular analysis) was worse compared to patients without micrometastases (10). Similar results were published by Xu et al (18)(19) and Yamazaki et al (21). Presence of unrecognized micrometastases or ones left in situ can also explain regional tumor recurrence in patients with N0 stage or in patients with N+ stage after selective neck dissection.…”
Section: Discussionmentioning
confidence: 60%
“…Nieuwenhuis et al found that the survival of patients with cN0 but with one or more micrometastases (detected by molecular analysis) was worse compared to patients without micrometastases (10). Similar results were published by Xu et al (18)(19) and Yamazaki et al (21). Presence of unrecognized micrometastases or ones left in situ can also explain regional tumor recurrence in patients with N0 stage or in patients with N+ stage after selective neck dissection.…”
Section: Discussionmentioning
confidence: 60%
“…[23][24][25][26] However, the previous studies did not address specifically the prognostic significance of p53 overexpression in the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that micrometastasis to regional lymph nodes leads to poor prognosis. 3 The presence of lymph node metastasis is one of the independent prognostic factors for predicting the outcome of patients with oral SCC. Tumor invasion and lymph node status are strongly correlated with a patient's survival.…”
Section: Introductionmentioning
confidence: 99%